HUBUNGAN DUKUNGAN SOSIAL DENGAN PENERIMAAN DIRI PASIEN PASCA STROK - Najoan, Kartika Tivani; Mulyadi, Ns; Kallo, Vandri (JURNAL KEPERAWATAN, 2016)
Abstrack :Between Social is a form of aid that could be material, emotional, and information provided by people who have meaning as family, friends, relatives, co-workers or loved by the individuals concerned. Self-acceptance is a condition in which individuals have confidence in himself characteristics, and are able and willing to live with the situation.The purpose of this study to analyze the relationship of social support with self-acceptance in post-stroke patients Sonder sub-district health centersThe method used is descriptive correlation with cross sectional design. The Sampling technique in this research is purposive sampling with 30 samples. Data is collected using a questionnaire. The results based on statistical test Chi-Square test with 95% significance level (Î± = 0.05) are presented in the table 2x2 obtained by value p = 0.000 which is smaller than Î± (0.05) with H0 rejected and Ha accepted. Conclusion there is a relationship of social support with self-acceptance in post-stroke patients Sonder sub-district health centers. Suggestion is expected to provide knowledge to families who have family members who suffer a stroke how social support that is given is salasatu things that can affect the healing process so that families can improve social endorsement that is provided tomembers of families affected by stroke. Keywords:Between Social, self-acceptance Abstrak:Dukungan Sosial adalah bentuk pertolongan yang dapat berupa materi, emosi, dan informasi yang diberikan oleh orang-orang yang memiliki arti oleh individu yang bersangkutan.Penerimaan Diri adalah suatukeadaan dimana individu memilikikeyakinan akan karakteristik dirinya, sertamampu dan mau untuk hidup dengankeadaan tersebut, Tujuan penelitian ini untuk menganalisa hubungan dukungan sosial dengan penerimaan diri pasien pasca strok di puskesmas kecamatan sonder. Metode penelitian yang digunakan yaitu deskriptif korelasi dengan rancangan cross sectional. Teknik Pengambilan Sampel pada penelitian ini yaitu purposive sampling dengan jumlah 30 sampel.Pengumpulan data dilakukan menggunakan kuesioner. Hasil penelitian berdasarkan uji statistik Chi-Square test disajikan dalam tabel 2x2 diperoleh nilai p = 0,001 yakni lebih kecil dibandingkan Î± (0,05) dengan H0 ditolak dan Ha diterima. Kesimpulan terdapat hubungan dukungan sosial dengan penerimaan diri pasien pasca strok di puskesmas kecamatan sonder.Saran diharapkan dapat memberikan pengetahuan kepada keluarga yang memiliki angota keluarga yang menderita strok bagaimana dukungan sosial yang di berikan merupakan salasatu hal yang dapat mempengaruhi proses penyembuhan. Kata Kunci: Dukungan Sosial Dengan Penerimaan Diri